Determination of Quercetin in Extracts and Herbal Products of Phyllanthus niruri by TLC Densitometry Method - Ihsan, Bachtiar Rifai Pratita; Delina, Ade Putri; Shalas, Alvan Febrian (Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR); Vol 2 (2022): Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR), 2022)
Phyllanthus niruri has many pharmacological activities such as antioxidant, anti-inflammatory and anticancer. Phyllanthus niruri has been widely developed from extracts into herbal products. The flavonoid quercetin became an analytical marker compound to ensure the quality of P. niruri extracts in the Indonesian herbal pharmacopeia II. This study aimed to determine the levels of quercetin in extract and herbal products using the TLC Densitometry method. TLC Densitometry method using chloroform: ethyl acetate: formic acid (5:4:1) as the mobile phase and silica GF254 as the stationary phase. The Rf value of the quercetin compound obtained is 0.50. The Rs quercetin is 1.56 in the extract and 2.55 in the product. The maximum wavelength for quercetin is 366 nm. The results of quercetin levels were 3.579% in the extract and 0.0412% in herbal products. The TLC densitometry method can analyze quercetin in extracts and herbal products.